Zionism and the melting pot : preachers, pioneers, and modern Jewish politics - Silver, M. M. (Matthew Mark), 1961- (Jews and Judaism : history and culture, 2020)
"Traces the roots of ideologies and outlooks that shape Jewish life in Israel and the United States today"--